KEANEKARAGAMAN DAN SEBARAN EKOLOGIS AMFIBI DI AIR TERJUN BARAMBAISAMARINDA, KALIMANTAN TIMUR - Jusmaldi Jusmaldi; Aditya Setiawan; Nova Hariani (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Diversity and ecological distributions of amphibians in Berambai Waterfall area, East Kalimantan have never been known. The purposes of this study were to determine the diversity of amphibian species in relation to environmental conditions and the vertical-horizontal distribution. A total of 109 amphibians were captured using methods of the transect and the visual encounter survey for 20 days on two type observation habitats. The results of this study found 18 species from six amphibian families. Based on the number of species, the diversity amphibian index and dominance index have a stable of communities, with the high value of Shannon-wiener diversity index (H'), the evenness index (E), and the low value of dominance index (D) were 2.26, 0.78, and 0.16, respectively. Horizontal distribution of amphibians in their habitat showed that aquatic amphibian groups were found to be less than 5 m from the river bank, while terrestrial and semi-aquatic amphibians have a distribution of 5–15 m from the river bank. Vertical distribution of Polypedates leucomystax, Polypedates otilophus and Odorrana hosii in vegetation were found from 1.5–2.5 m above ground level, while Ansonia spinulifer, Chalcorana chalconota, Chalcorana raniceps were at a height of 0.5–<1.5 m from ground level. Diversity of amphibian in Berambai Waterfall area related to habitat conditions, while horizontal and vertical distributions are influenced by species, habits and food resources.